2016
DOI: 10.1093/toxsci/kfw260
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analyses of volatile organic compounds in obstructive sleep apnea patients

Abstract: Various volatile organic compounds (VOCs) are known to be toxic. Although exhaled VOC patterns change in obstructive sleep apnea (OSA) patients, individual VOC profiles are not fully determined. The primary outcome was VOC characterizations; secondary outcomes included their relationships with sleep and clinical parameters in OSA patients. We prospectively examined 32 OSA patients with an apnea-hypopnea index (AHI) ≥ 15 by full polysomnography, and 33 age- and sex-matched controls without obvious OSA symptoms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…However, none of the compounds described by Greulich were also identified by Dragonieri and colleagues, who reported a good discriminative capacity between OSAS and obese controls basing on the following compounds: tetrachloroethene, 2,3,5-trimethylhexane, β-pinene, 1,3,5-trimethylbenzene, 9-methylacridine, tetradecane, 6,10-dimethyl-5,9-undecadien-2-one and β-ionone [61]. Besides, Aoki and colleagues found that although almost all the aromatic and satured hydrocarbons are more expressed in the exhaled breath of severe OSAS patients, only isoprene is always elevated in OSAS, regardless the severity of the disease [62].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of the compounds described by Greulich were also identified by Dragonieri and colleagues, who reported a good discriminative capacity between OSAS and obese controls basing on the following compounds: tetrachloroethene, 2,3,5-trimethylhexane, β-pinene, 1,3,5-trimethylbenzene, 9-methylacridine, tetradecane, 6,10-dimethyl-5,9-undecadien-2-one and β-ionone [61]. Besides, Aoki and colleagues found that although almost all the aromatic and satured hydrocarbons are more expressed in the exhaled breath of severe OSAS patients, only isoprene is always elevated in OSAS, regardless the severity of the disease [62].…”
Section: Resultsmentioning
confidence: 99%
“…Albeit apparently contradictory, it is possible that the association between AHI and breath pattern is mediated by patients’ comorbidities, as suggested by Incalzi and colleagues [67]. Breath-pattern is sensitive to the effects of the C-PAP therapy, indeed concentrations of isoprene and acetone decrease [62] and it is possible to discriminate treated and untreated patients with good accuracy [68]; even a single night treatment is associated with a change in the breath pattern. Interestingly, the breath pattern change does not have the same characteristics in all OSAS patients, with two different types of response being distinguished depending on the comorbidities of those individuals [67].…”
Section: Resultsmentioning
confidence: 99%
“…Metabolomic approaches have been applied in the study of OSA, whereby they can be categorized into two types of studies, including (1) metabolomic studies of exhaled breath [ 38 , 39 , 40 ], and (2) studies of the blood and/or urine metabolome [ 41 , 42 , 43 , 44 ].…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
“…Markers of chronic inflammation were enhanced, showing an increase in pro-inflammatory cytokines, while anti-inflammatory cytokines decreased [ 47 ]. Furthermore, elevations of toxic volatile organic compounds in patients with OSA were observed [ 38 ]. More specifically, aromatic hydrocarbons (phenylacetic acid, ethylbenzene, toluene and p-xylene), saturated hydrocarbons (hexane, octane, heptane, nonane and decane), acetone and isoprene were elevated, which have been suggested as potential biomarkers.…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
“…Because of the nonspecific nature of electronic nose measurements, the individual molecules responsible for the differences in OSA are not known. Elevated levels of exhaled butanol [74], toluene, ethylbenzene, p-xylene, phenylacetic acid, hexane, heptane, octane, nonane, decane, acetone, and isoprene [75] as well as an overnight increase in exhaled pentane [64] were reported in OSA. In addition, CPAP withdrawal resulted in alterations in the concentrations of several volatile organic compounds [76].…”
Section: Airway Inflammationmentioning
confidence: 98%